'If the change is going to happen it's not by us': Exploring the role of NGOs in the politicization of Ugandan agriculture. (October 2018) - Isgren, Ellinor
Abstract: Sustainable agricultural development that prioritizes the needs and respects the rights of smallholder farmers is widely framed as a societal goal by both national governments and international institutions. However, in many places this remains an elusive goal, not least in sub-Saharan Africa. The past decades have seen new types of rural social movements emerge, demanding socially just and environmentally sustainable trajectories of agrarian change. But there are also places where this is seemingly not the case, Uganda being one. Based on qualitative research involving civil society organizations at the national and regional level, this paper analyzes contemporary civil society dynamics around agriculture in Uganda against a historical backdrop. Social division and civil society NGOization have contributed to unfavorable conditions for rural social movement emergence, but not irreversibly. Systematic policy advocacy engagement appears to be on the rise amongst agriculture-oriented NGOs, and while it is generally non-confrontational, contentious claims-making does happen. NGOs also aspire to facilitate farmer-led mobilization, although their logics of intervention differ and would benefit from more dialogue and theoretical grounding. For moving forward in NGOized contexts like Uganda, three points are emphasized: NGO-led and farmer-led mobilization is not a simple dichotomy; their relationship need not be antagonistic and there are several possible ways to seek synergies; and fostering capacity for farmers' contentious claims-making must involve counterhegemonic struggle. The paper ends by suggesting three areas for agri-food scholars interested in the complex interactions between NGOs and rural social movements. Highlights: Rural social movements play an important role in agrarian politics in many places. In Uganda, barriers include NGOization, conflict and state co-optation/repression. Although limited, NGOs have several roles to play in politicization of agriculture. This includes both strategic policy advocacy and farmer mobilization. Key research areas for critically-engaged agri-food scholarship are outlined.